1990
DOI: 10.1093/oxfordjournals.humrep.a137094
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between human sperm acrosin, acrosomes, morphology and fertilization in vitro

Abstract: Acrosin was measured in the semen used for sperm preparation for in-vitro fertilization (IVF) in 118 patients. Acrosin levels correlated with the proportion of spermatozoa with normal intact acrosomes determined with Pisum sativum agglutinin labelled with fluorescein. However, acrosin levels and the proportion of spermatozoa with normal intact acrosomes in semen were not significantly related to the fertilization rate in vitro. Only the percentage normal morphology and sperm concentration in the insemination m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 0 publications
2
32
0
Order By: Relevance
“…As cell count is used as the denominator, it is noteworthy that the calculated activity may be subject to technical errors, especially for low sperm densities (<5 X 10 6 spermatozoa/ml). Results of this study agree with those of Kruger et al (1988) and Liu and Baker (1990), who found no relationship between acrosin activity and fertilization in vitro. There is no doubt that this enzyme plays a critical role during zona binding and zona penetration (Tesarik et al, 1988) but its action is dependent on structural and biochemical events which take place during capacitation and the acrosome reaction.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As cell count is used as the denominator, it is noteworthy that the calculated activity may be subject to technical errors, especially for low sperm densities (<5 X 10 6 spermatozoa/ml). Results of this study agree with those of Kruger et al (1988) and Liu and Baker (1990), who found no relationship between acrosin activity and fertilization in vitro. There is no doubt that this enzyme plays a critical role during zona binding and zona penetration (Tesarik et al, 1988) but its action is dependent on structural and biochemical events which take place during capacitation and the acrosome reaction.…”
Section: Discussionsupporting
confidence: 93%
“…However, an attempt to assess the specificity of the acrosin antibody was performed by comparing the immunofluorescence scores with the acrosin activity determined on the sperm samples used for IVF (Figure 3). A significant correlation was found, although the acrosin activities were subject to large fluctuations from sample to sample (Kennedy et al, 1989;Liu and Baker, 1990). Unlike Kennedy et al (1989), we were unable to find any clear threshold value below which fertilization would fail (Table VI).…”
Section: Discussionmentioning
confidence: 65%
“…The association was not restricted to any one particular classification system and/or evaluation procedure. Some of these studies also showed that this association was independent of any of the other semen parameters [11,12,16,20,21] . It is of utmost importance to obtain good quality control in a laboratory evaluating sperm morphology.…”
Section: Literature Reviewmentioning
confidence: 90%
“…47 Observations made in a previous study concluded that sperm morphology is closely correlated with specific sperm functions. 48,49 Furthermore, Esterhuizen et al 50 point out that sperm morphology evaluation, especially the configuration of the acrosome, is a good method to estimate sperm fertilizing ability. Understandably, this relationship is closest if the physiological inducer, zona pellucida, is used to induce acrosome reaction for diagnostic purposes.…”
Section: Sperm Function Testingmentioning
confidence: 99%
“…It is well documented that these assays provide important evidence on one of the recognition events leading to fertilisation. 47,49,76 Significant factors affecting the validity of both these assays include oocyte sources and maturation, inter-assay and intra-assay variability, sperm motility, morphology and acrosomal status. 45 …”
Section: Acrosome Reactionmentioning
confidence: 99%